Desain Karakter sebagai Media Komunikasi Visual untuk Edukasi Kesehatan Mata Anak terhadap Penggunaan Gadget - Amalia Khasanah; Aileena Solicitor Costa Rica El Chidtian; Aninditya Daniar (Universitas Dian Nuswantoro, 2026)
The habit of staring at gadget screens for long periods can cause eye health problems, such as eye fatigue, dry eyes, and the risk of early myopia. This study aims to design character designs as a visual communication medium in conveying eye health education to early childhood. The method used is a qualitative descriptive approach with data collection techniques, through observation, questionnaires, interviews, and literature studies. The design result in three main character designs, namely Aksi, Ema, and dr. Lensa. This design shows that a visual approach trough character designs that are close to the world of children can help convey educational messages that are interesting, communicative, and easy to understand.